Assessing the relationship of work space environment on the health and wellness of employees in Davao and Tagum City Hall - Campo, Frances Ianelle L. (2021)
Sick Building Syndrome (SBS) has been a common health issue among occupants occupying a building with poor indoor environment quality. This could lead to poor performance, increased absenteeism, low productivity, and high cost for the company they are working in. Workers in office environments where tasks are repetitive experience this kind of health issue. The current study was designed to assess the present condition of work space environments in Davao and Tagum City Hall and identify how these environments are linked to the health and wellness of employees. Data was obtained through key informant interviews with medical experts, survey questionnaires, and work space environment assessment. The work spaces of Davao and Tagum City Hall were evaluated using an assessment tool that was adapted from the WELL Building Standards. Results revealed that the most reported symptoms in the offices of both city halls respiratory and eye irritation symptoms. Work space environment assessment showed that the performance of Davao City Hall work environments ranged from FAIR to POOR while the performance of Tagum City Hall work environments ranged from FAIR to GOOD. These were triangulated with the key informant interview which suggested that the most reported symptoms were observed in work spaces that failed to meet specific criteria in the assessment. This research highlights the importance of designing work environments that supports the health and wellness of occupants. With this, the translation of the study integrated health-promoting features in the design of the proposed project.